Peningkatan Akurasi Stock Opname Material Local Parts Menggunakan CCM, FMEA, dan FTA: Sebuah Studi tentang Pengendalian Persediaan dan Ketepatan Penghitungan Stok - Cinta Cinta; Mochamad Eko Nugroho; Lifia Citra Ramadhanti (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2026)
Inventory is an important asset that supports the continuity of production processes in manufacturing companies. One of the common problems is the discrepancy between physical inventory and system records during stock opname activities, which may cause financial losses and reduce inventory accuracy. This study aims to identify the causes of stock opname discrepancies and improve inventory accuracy of Local Parts materials at PT Inoi Mobile Indonesia (IMI). The methods applied in this research include Failure Mode and Effect Analysis (FMEA), Cycle Counting Method Method (CCM) with ABC classification, and Fault Tree Analysis (FTA) based on the 5W+1H approach. Data were collected through observation, interviews, and company stock opname records. The results indicate that the main causes of inventory discrepancies are recording errors, operator negligence, and weak implementation of standard procedures. FMEA analysis shows that non-real-time material issuing has the highest Risk Priority Number (RPN), making it the primary improvement priority. ABC analysis reveals that category A materials contribute the highest cost impact on the company. Furthermore, FTA systematically identifies the root causes of stock discrepancies. The integration of these methods is proven to improve inventory accuracy and effectively reduce stock opname discrepancies.